Analisis Kinerja Keuangan antara PT Bank Mandiri (Persero) Tbk dan PT Bank Capital Indonesia Tbk Periode 2014–2023 berdasarkan Rasio Profitabilitas dan Solvabilitas - Ramadhan, M Fikri; Puji Muniarty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze and compare the financial performance of PT Bank Mandiri (Persero) Tbk and PT Bank Capital Indonesia Tbk during the period 2014–2024 based on profitability and solvency ratios. The method used in this research is quantitative descriptive analysis using secondary data obtained from annual financial reports. The profitability ratios analyzed include Return on Assets (ROA) and Return on Equity (ROE), while solvency is measured using the Capital Adequacy Ratio (CAR) and Debt to Equity Ratio (DER). The results show that Bank Mandiri consistently demonstrates higher profitability compared to Bank Capital Indonesia, reflecting better asset management and operational efficiency. In terms of solvency, both banks maintain adequate capital levels, but Bank Mandiri shows stronger financial resilience. This study contributes to understanding financial performance differences between large state-owned banks and smaller private banks.